School Well-Being Among Children and Adolescents: Assessing Strategies for Bullying Prevention in Madrasahs - Shobihah, Ida Fitri (Institut Agama Islam Daruttaqwa Gresik, 2025)
. Students' sense of comfort at school is the foundation for achieving well-being within the school environment. This well-being encompasses various aspects of students' lives, including physical, emotional, social, and personal dimensions. When a school fails to foster such well-being, it can increase the risk of bullying behaviors among students. Therefore, this study aims to analyze school well-being among children and adolescents, as well as to assessing strategies for bullying preventing bullying in Madrasahs. This research employed a qualitative method with an indigenous psychology approach. Data were collected in two stages: survey with open ended questionnaire and interviews. The survey involved 100 elementary-level (MI) students and 61 junior high-level (MTs) students. Interviews were conducted with school principals and counseling teachers. The results revealed that school well-being among both children and adolescents consists of four main aspects: having, loving, being, and health. However, differences emerged in the relational emphasis: for children, well-being strongly related to interactions with peers, teachers, and parents, while for adolescents, peer relationships were the dominant factor. The bullying prevention strategy implemented by the madrasah involves innovative programs for self-development, including the provision of guidance and counseling services, the establishment of routine school-wide activities, and the adequate provision of facilities. These three components constitute aspects of school well-being and play an effective role in regulating students’ behavior.